EFEKTIVITAS PEMBELAJARAN BAHASA ARAB DENGAN MENGGUNAKAN METODE EKLEKTIK DI MIN 10 DUREN SAWIT - Fatkhur Roji (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2024)
This study aims to determine how the effectiveness of learning Arabic by using the MIN 10 Duren Sawit Direct Class Method. Based on the findings in the field that students' abilities differ in understanding Arabic learning material. There are still students who are less skilled and less enthusiastic when the learning process takes place. This can be seen from the process and the results obtained by the student. Location This research was conducted at MIN 10 Duren Sawit in the 2023 academic year. The sample in this study were Arabic language teachers and students namely as many as 71 respondents in MIN 10 Duren Sawit. The method used is a descriptive qualitative data analysis technique that is deductive in nature with a sample of MIN 10 Duren Sawit III grade students. From the calculation obtained the direct method effectiveness percentage is 66.2 which if interpreted in the qualitative sentence, the number is at the rate of 56%— 75% which means enough. So, the quality of the direct method in class III at MIN 10 Duren Sawit is in a sufficient position